A prospective study on prognostic value of ventilatory efficiency in asymptomatic patients with severe primary mitral regurgitation. - Johannes Bergsten; Tomasz Baron; Eva-Maria Hedin; Nermin Hadziosmanovic; Andrei Malinovschi; Frank A Flachskampf (PLoS ONE, 2025)
Objectives Patients with severe primary mitral regurgitation (PMR) remain asymptomatic at first. In the long term, however, severe PMR leads to cardiac decompensation. Exercise testing in asymptomatic PMR is recommended in selected patients by guidelines. Cardiopulmonary exercise testing (CPET), which additionally measures ventilation (VE), oxygen consumption (VO2) and carbon dioxide production (VCO2), has been scarcely studied in PMR. We hypothesized that CPET might have prognostic value in asymptomatic PMR and therefore studied if CPET, including assessment of ventilation efficiency, has prognostic value for asymptomatic patients with severe PMR. Methods Asymptomatic patients with severe PMR were prospectively recruited between 2013 and 2018. Exclusion criteria were coronary artery disease, chronic kidney disease, diabetes mellitus, concomitant valve disease, symptomatic lung disease or class 1 recommendation for valvular surgery. Echocardiography and serial CPET were conducted at one university hospital in Sweden. Primary outcome was mitral valve intervention. Results Forty-eight patients were recruited to the study. Median follow-up period was 4.4 (2.1-6.9) years, during which 28 (58%) patients underwent mitral valve surgery. Ventilation efficiency, the relationship of VE to VCO2 during CPET, predicted surgical treatment of the mitral valve. Increased VE/VCO2 ratio at the anaerobic threshold had the highest predictive value, remaining an independent predictor after adjusting for impaired VO2 at peak exercise (HR 4.42 (1.52-12.92), p = 0.007) and echocardiographic thresholds for left ventricular and atrial remodelling, as defined by current guideline-based recommendation for intervention (HR 3.72 (1.41-9.82), p = 0.008). Conclusion Impaired ventilatory efficiency, but not peak VO2, predicted surgical treatment of the mitral valve in asymptomatic patients with severe PMR. Ventilatory efficiency, a CPET index less dependent on peak exercise performance, may be a new useful tool in risk stratification.